Stratigraphic and technological evidence from the Middle Palaeolithic-Châtelperronian-Aurignacian record at the Bordes-Fitte rockshelter (Roches d'Abilly site, Central France) - Aubry, Thierry (2012)
This paper presents a geoarchaeological study of Middle and Upper Palaeolithic (Châtelperronian, Aurignacian and Solutrean) occupations preserved at the Bordes-Fitte rockshelter in Central France. The lithostratigraphic sequence is composed of near-surface sedimentary facies with vertical and lateral variations, in a context dominated by run-off and gravitational sedimentary processes. Field description and micromorphological analysis permit us to reconstruct several episodes of sediment slope-wash and endokarst dynamics, with hiatuses and erosional phases. The archaeostratigraphic succession includes Châtelperronian artefacts, inter-stratified between Middle Palaeolithic and Aurignacian occupations. Systematic refitting and spatial analysis reveal that the Châtelperronian point production and flake blanks retouched into denticulates, all recovered in the same stratigraphic unit, result from distinct and successive occupations and are not a 'transitional' Middle to Upper Palaeolithic assemblage. The ages obtained by (14)C place the Châtelperronian occupation in the 41-48 ka cal BP (calibrated thousands of years before present) interval and are consistent with the quartz optically stimulated luminescence age of 39 ± 2 ka and feldspar infra-red stimulated luminescence age of 45 ± 2 ka of the sediments. The Bordes-Fitte rockshelter sequence represents an important contribution to the debate about the characterization and timing of the Châtelperronian, as well as its affinities to earlier and later industries.